Injectable anesthesia in farm animals - Lionel Dawson (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Injectable anesthesia in farm animals been used on a routine basis in academia and in clinical practice in the United States of America. As an ambulatory clinician, the author has used various pharmaceuticals and combinations for sedation and short term generalized anesthesia, on farm animals in performing various techniques, clinical procedures,major and minor surgeries in the clinic and on the farm. There are many physical and mental challenges in dealing with farm animals when safely restraining or immobilizing them for any surgical or non-surgical procedures performed. The main goal is to effectively control the animal without injuring the /to subject/animal or the personnel involved. In most cases, for performing physical examination or minor surgery a chute, crush, ropes, or local anesthesia is sufficient to accomplish the task. However, on certain situations, sedatives, dissociative, and systemic analgesics can provide the mental distraction needed to reduce reflex reactions and override learned behaviors. This article will review some of the common uses of sedation and anesthesia in performing both minor and major surgeries using injectable anesthetic drugs in farm animals.